Adenomatoid tumors of the epididymidis: clinical and pathomorphological analysis of a case - T. S. Mukhina; A. V. Tverskaya; V. V. Fentisov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Objective. To present the clinical and pathomorphological analysis of a rare case of adenomatoid tumor of the epididymis with a description of the diagnostic and morphological characteristics of this neoplasm. Materials and methods. A comprehensive examination was conducted on a 41-year-old patient with a painless mass in the left half of the scrotum, including clinical examination, ultrasound, magnetic resonance imaging, biochemical blood analysis for tumor markers, and histopathological examination of the surgical specimen using routine (hematoxylin and eosin staining) and immunohistochemical methods (detection of pancytokeratin AE1/AE3, calretinin, CD31, and D2-40 expression).Results. A solid yellowish mass, 2 cm in diameter, originating from the head of the left epididymis was found in the patient. Histologically, the tumor was represented by chains of cells, clusters, trabeculae, and gland-like structures formed by large cells with epithelioid morphology. Immunohistochemical examination revealed pronounced cytoplasmic coexpression of pancytokeratin AE1/AE3 and calretinin, absence of CD31 expression, and positive membrane reaction to D2-40 (podoplanin), confirming the mesothelial origin of the tumor.Conclusion. Adenomatoid tumor of the epididymis is a rare benign tumor of mesothelial origin that cannot be accurately verified by clinical, instrumental, and laboratory data alone. Pathomorphological examination with mandatory immunohistochemical analysis is crucial for diagnosis, allowing the establishment of the mesothelial histogenesis of the tumor. Surgical treatment with excision of the tumor node within healthy tissue margins is an adequate and sufficient method of therapy, leading to complete recovery.